Using FT-IR Spectroscopy to Measure Charge Organization in Ionic Liquids - Burba, Christopher M. (2013)
A major goal in the field of ionic liquids is correlating transport property trends with the underlying liquid structure of the compounds, such as the degree of charge organization among the constituent ions. Traditional techniques for experimentally assessing charge organization are specialized and not readily available for routine measurements. This represents a significant roadblock in elucidating these correlations. We use a combination of transmission and polarized-ATR infrared spectroscopy to measure the degree of charge organization for ionic liquids. The technique is illustrated with a family of 1-alkyl-3-methylimidazolium trifluoromethansulfonate ionic liquids at 30°C. As expected, the amount of charge organization decreases as the alkyl side chain is lengthened, highlighting the important role of short-range repulsive interactions in defining quasilattice structure. Inherent limitations of the method are identified and discussed. The quantitative measurements of charge organization are then correlated with trends in the transport properties of the compounds to highlight the relationship between charge and momentum transport and the underlying liquid structure. Most research laboratories possess infrared spectrometers capable of conducting these measurements, thus, the proposed method may represent a cost-effective solution for routinely measuring charge organization in ionic liquids.